Development and validation of the educational psychological capital scale - Ooh Seow Ling; Irmadura Ramli; Cheah Seeh Lee; Ooi Chia-Yi; Ch’ng Ping Ping; Surianti Lajuma (Institute of Advanced Engineering and Science, 2024)
Since the introduction of psychological capital to the field of education, it has drawn a lot of interest from researchers. This is due to the numerous studies that have demonstrated the positive effects of psychological capital on academic performance. Nevertheless, the psychological capital scale was initially developed to measure the psychological capital of employees, not students. There is a dearth of studies that examine the psychological capital scale’s psychometric properties in educational contexts, particularly in Southeast Asia. Therefore, the present study aims to develop and test the validity of an educational psychological capital scale. The study was carried out with the participation of a total of 2,494 undergraduates. The tests of indicator reliability, construct reliability convergent, validity, and discriminant validity were executed. The result revealed that the scale demonstrated satisfactory psychometric properties. The study also found psychological capital can serve as a positive predictor of student academic performance. It signified that the scale can be used to measure student psychological capital precisely. This has resolved the flaw of the original psychological capital scale, which measured students’ psychological capital in the workplace rather than in educational settings. However, since the study was conducted in Malaysia, the psychometric properties of the scale can be further verified in other countries.